2017
DOI: 10.1128/mcb.00424-16
|View full text |Cite
|
Sign up to set email alerts
|

NDR1-Dependent Regulation of Kindlin-3 Controls High-Affinity LFA-1 Binding and Immune Synapse Organization

Abstract: Antigen-specific adhesion between T cells and antigen-presenting cells (APC) during the formation of the immunological synapse (IS) is mediated by LFA-1 and ICAM-1. Here, LFA-1–ICAM-1 interactions were measured at the single-molecule level on supported lipid bilayers. High-affinity binding was detected at low frequencies in the inner peripheral supramolecular activation cluster (SMAC) zone that contained high levels of activated Rap1 and kindlin-3. Rap1 was essential for T cell attachment, whereas deficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 67 publications
3
66
0
Order By: Relevance
“…Kinashi's group further identified that NDR1 kinases, after being activated by the RAP1-RAPL-MST1 signaling cascade, associated with and recruited kindling-3 to the immune synapse, which was required for high-affinity LFA-1/ ICAM-1 binding and immune synapse formation. 40 Meanwhile, we demonstrated that MST1/2-deficient thymocytes lacked the ability to activate rho family GTPases such as Rac and RhoA, and then exhibited defects in cytoskeletal regulation processes that are necessary for thymic egress of mature thymocytes. 15 Thymocytes express multiple guanine nucleotide exchange factors (GEFs) for Rac, including DOCK8.…”
Section: T-cell Adhesion and Migration Unlike The Canonical Hippo-latmentioning
confidence: 97%
“…Kinashi's group further identified that NDR1 kinases, after being activated by the RAP1-RAPL-MST1 signaling cascade, associated with and recruited kindling-3 to the immune synapse, which was required for high-affinity LFA-1/ ICAM-1 binding and immune synapse formation. 40 Meanwhile, we demonstrated that MST1/2-deficient thymocytes lacked the ability to activate rho family GTPases such as Rac and RhoA, and then exhibited defects in cytoskeletal regulation processes that are necessary for thymic egress of mature thymocytes. 15 Thymocytes express multiple guanine nucleotide exchange factors (GEFs) for Rac, including DOCK8.…”
Section: T-cell Adhesion and Migration Unlike The Canonical Hippo-latmentioning
confidence: 97%
“…There, active CrkII recruited the GEF C3G, which activated the small GTPase Rap-1 (Ras-associated protein 1). Kondo and co-workers delineated that Rap-1 via Mst1/Mst2 activated NDR (Nuclear Dbf2-Related Kinase) 1 kinase [142]. In APC-binding T cells, Rap-1 activation was mediated in part by PI3Kδ [143].…”
Section: Regulation Of Lfa-1 Activity On T Cellsmentioning
confidence: 99%
“…This resulted in impaired activation of LFA-1, and attenuated IS formation. Activated NDR1 engaged Kindlin-3 and mediated its translocation towards the cSMAC [142]. The LFA-1 binding coactivator Kindlin-3 is defective in LAD-III patients [40].…”
Section: Regulation Of Lfa-1 Activity On T Cellsmentioning
confidence: 99%
“…It is reported that Rap1 is activated by TCR or chemokine signals, and then recruits SARAH domain-mediated-hetero-dimerization Mst1/RAPL controls Mst1 localization and activation at the membrane, facilitating the activation of LFA-1. Of note, it is reported that kindlin-3 regulated by active Mst1 via NDR1/2 interacts with cytoskeleton at the inner pSMAC to regulate the formation and stability of immunological synapse ( 41 ). However, the underlying mechanism needs more explanation.…”
Section: Mst1 Associated With Lfa-1 Controls the Migration Of Lymphocmentioning
confidence: 99%
“…Mst1 also organizes the immunological synapse by the regulating vesicle transport of the TCR to the cSMAC. Indeed, VSP4, a biomarker of TCR-enriched vesicle ( 48 ), and Rab8 or Rab11, proteins that mediate TCR vesicle transport ( 41 , 49 ), are not enriched at the immunological synapse in Mst1/2-deficient T cells.…”
Section: Mst1 Associated With Lfa-1 Controls the Migration Of Lymphocmentioning
confidence: 99%